Determinants of Basic Immunization Coverage: The Role of Family Knowledge and Support in Central Sulawesi, Indonesia - Abustam; Ullah, Tariq (International Journal of Health Concord, 2025)
Background: Indonesia continues to face challenges in achieving optimal immunization coverage, especially in rural and underserved regions. In Central Sulawesi, incomplete basic immunization among children remains prevalent despite government programs. This study aimed to investigate the role of maternal knowledge and family support in predicting complete basic immunization coverage among children aged 1–5 years in Toili II Community Health Center, Banggai Regency. Methods: A cross-sectional correlational study was conducted in August 2024 using a non-probability sampling method. A total of 53 mothers participated. Data were collected using validated and reliable questionnaires measuring maternal knowledge (18 items) and family support (15 items). Immunization status was verified using vaccination cards. Data analysis involved descriptive statistics, bivariate Chi-square tests, and multivariate logistic regression. Result: Results showed that 64.2% of children had complete immunization. Nearly half of the mothers had moderate knowledge (49.1%) and moderate family support (39.6%). Logistic regression revealed that both maternal knowledge (p < 0.001) and family support (p < 0.001) were significant independent predictors of complete immunization. Together, they explained 85.9% of the variance in immunization status. Conclusion: This study concludes that maternal knowledge and family support significantly and synergistically influence childhood immunization completeness. Health promotion strategies should integrate family-based education and support systems into immunization programs, particularly in rural areas. Frontline health workers are encouraged to assess both knowledge and perceived support during routine visits. Policymakers should consider embedding family-engagement modules in immunization guidelines and leveraging household dynamics to strengthen national immunization coverage.